Ethical Challenges Of Ai-Assisted Efl Learning: A Library Research On Students’ Academic Integrity - Zahrotul Aini Musyarofah; Naura Ariesta; Ria Anggraeni; Alisa Maharani Husaen (Tarling : Journal of Language Education, 2026)
Background - The increasing use of Artificial Intelligence (AI) in English as a Foreign Language (EFL) learning has transformed language learning and academic writing practices. While AI offers valuable learning support, its growing presence in academic work also raises concerns regarding academic integrity and ethical conduct. Urgency of Research - Despite the growing use of AI in EFL learning, the ethical challenges of AI use in EFL contexts remain insufficiently synthesized. Research Objectives - This study examines these challenges, particularly regarding academic integrity, authorship, originality, and responsible AI use in higher education. Research Method - Using a library research approach, this study reviews and synthesizes relevant scholarly literature published between 2018 and 2024. Research Findings - The findings reveal three major ethical concerns: the blurred boundary between legitimate AI assistance and academic misconduct, challenges to traditional notions of authorship and originality, and the lack of clear institutional policies governing AI use. The review also highlights the tension between AI as a learning support tool and as a shortcut for task completion. Research Conclusion & Novelty - This study contributes an EFL-specific synthesis of ethical issues and emphasizes the importance of AI literacy, transparent usage practices, and context-sensitive policies to support responsible AI integration while maintaining academic integrity.